2011
DOI: 10.4028/www.scientific.net/amr.222.32
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Doping of CdTe Crystals in Different Environments

Abstract: Different procedures of laser-induced doping of the surface region of semi-insulating CdTe semiconductor are discussed. CdTe crystals pre-coated with an In dopant film were subjected to irradiation with nanosecond laser pulses in different environments (vacuum, gas or water). The dopant self-compensation phenomenon was overcome under laser action and In impurity with high concentration was introduced in a thin surface layer of CdTe. In the case of a thick (300-400 nm) In dopant film, laser-induced shock wave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…The whole surface area of the CdTe crystal pre-coated with an In film was entirely and uniformly irradiated with nanosecond laser pulses at room temperature ( Figure 7 b). It was shown that distilled water environment was the optimal ambient condition for such treatment [ 55 ]. A KrF excimer laser, emitting single pulses with a wavelength of 248 nm and duration of 20 ns, was a pulsed radiation source.…”
Section: Capabilities Of Cdte-based X/γ-ray Detectors With An In Contact Treated By Laser Pulse Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The whole surface area of the CdTe crystal pre-coated with an In film was entirely and uniformly irradiated with nanosecond laser pulses at room temperature ( Figure 7 b). It was shown that distilled water environment was the optimal ambient condition for such treatment [ 55 ]. A KrF excimer laser, emitting single pulses with a wavelength of 248 nm and duration of 20 ns, was a pulsed radiation source.…”
Section: Capabilities Of Cdte-based X/γ-ray Detectors With An In Contact Treated By Laser Pulse Radiationmentioning
confidence: 99%
“…The use of a relatively thick In electrode (0.3–0.5 µm), which also served as an dopant film, made it possible to ensure laser-induced doping without heating the underlying bulk In region and CdTe crystal that avoided a heat-induced deterioration of the structure and properties of the semiconductor. Despite the fact that absorption of laser radiation occurred in a thin (tens of nanometers) In surface layer, the thin semiconductor region under the In/CdTe interface was heavily doped with In atoms [ 55 , 56 ]. It was supposed that In/CdTe/Au diode structures with an In doped CdTe nano-layer and built-in p-n junction were obtained as a result of laser-stimulated modification of the defect structure and solid-phase doping in the deep-seated CdTe region.…”
Section: Capabilities Of Cdte-based X/γ-ray Detectors With An In Contact Treated By Laser Pulse Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser processing of CdTe has been successfully used to modify the structure and properties of surface nano-layers and change different characteristics of the semiconductor. Of particular interest is application the laser assisted doping technique to suppress the dopant self-compensation mechanism, and reach introducing and efficient electrical activation of In atoms in CdTe [5][6][7][8][9][10]. We have continued development and optimization the methods of chemical surface processing of CdTe crystals, laser induced doping technique for creation of a built-in p-n junction by nanosecond laser irradiation of the CdTe crystals precoated with a relatively thick In film which serves both as an n-type dopant source and electrical contact (electrode) after the doping and deposition of the second electrode [7][8][9][10].The formation of a surface nano-layer highly-doped with In in semi-insulating detector-grade p-like CdTe crystals and creation of In/CdTe/Au diodes with a shallow and sharp p-n junction has been studied and mechanism of laser-induced doping is analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of another etching solution also results in contamination of the crystal surface with chemical reaction products. Recently, pulsed laser irradiation has been successfully used for surface processing of CdTe crystals [6][7][8][9][10] . However, in this case the laser-treated surface of CdTe crystal as becomes enriched with Te 10 .…”
Section: Introductionmentioning
confidence: 99%